1348 A QUALITY IMPROVEMENT PROJECT TO IMPROVE ASSESSMENT AND DOCUMENTATION FOLLOWING INPATIENT FALLS. (16th January 2023) - White, G; Roberts, A; Taylor, A; Graham, A; Parkin, K; Kotta, P; Fleet, J
Abstract: Introduction: Inpatient falls are a major cause of avoidable harm in patients on elderly care wards. Delays in identification of fall precipitants and recognition of sustained injuries increases morbidity, mortality and length of stay (Cameron et al, Cochrane Database Syst Rev. 2018 Sep; 2018(9)). Patients sustaining falls are often initially assessed by postgraduate year 1 and 2 doctors independently. We aimed to improve patient outcomes following inpatient falls through standardisation of the assessment and documentation following a fall in hospital. Methods: Using PDSA methodology, incident reports and documentation of inpatient falls were reviewed retrospectively over three 28-bedded elderly care wards. A post-falls proforma was devised that covered various domains of the post-fall assessment and was distributed to doctors throughout the hospital. Following the intervention, a repeat PDSA cycle was performed prospectively over the same wards and the proportion of assessments fulfilling each domain was compared between the cycles. Results: Medical assessment of 27 falls from November 2020 to January 2021 was compared to 31 falls occurring between February and May 2022. Use of the proforma in cycle 2 was limited to 8/31 falls following intervention. Post-intervention, the proportion of assessments fulfilling medication review (19% vs 35%, p=0.14) and anticoagulation status (41% vs 55%, p=0.28) was improved. The proportion fulfilling fall circumstances (89% vs 90%, p=0.85), medical precipitant (70% vs 61%, p=0.46) and ordering of appropriate imaging (93% vs 97%, p=0.47) remained high. Conclusion: Standardisation of post-falls assessment and documentation can improve patient safety outcomes through reducing delay in recognition of medical precipitants of falls and identification and management of sustained injuries. Improved integration of a post-falls proforma into electronic systems is needed to maximise its clinical benefit and would be the target of a further PDSA cycle.